2014
DOI: 10.1073/pnas.1400049111
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic switching in gene regulatory networks

Abstract: Noise in gene expression can lead to reversible phenotypic switching. Several experimental studies have shown that the abundance distributions of proteins in a population of isogenic cells may display multiple distinct maxima. Each of these maxima may be associated with a subpopulation of a particular phenotype, the quantification of which is important for understanding cellular decision-making. Here, we devise a methodology which allows us to quantify multimodal gene expression distributions and single-cell p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
180
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4
2

Relationship

2
8

Authors

Journals

citations
Cited by 178 publications
(187 citation statements)
references
References 24 publications
6
180
0
1
Order By: Relevance
“…5 of Ref. [34]), we have shown that no such stimulus is needed in the presence of fast switching conditions (transient bimodality in phases 3 and 4). Furthermore we have shown that this mechanism does not rely on cooperativity and is enhanced when protein expression is sufficiently bursty, that is when many proteins are produced from a single mRNA copy, a fairly common scenario in eukaryotic cells because of the long lifetimes of eukaryotic mRNA and large translation rates [35,36].…”
Section: Summary and Discussionmentioning
confidence: 66%
“…5 of Ref. [34]), we have shown that no such stimulus is needed in the presence of fast switching conditions (transient bimodality in phases 3 and 4). Furthermore we have shown that this mechanism does not rely on cooperativity and is enhanced when protein expression is sufficiently bursty, that is when many proteins are produced from a single mRNA copy, a fairly common scenario in eukaryotic cells because of the long lifetimes of eukaryotic mRNA and large translation rates [35,36].…”
Section: Summary and Discussionmentioning
confidence: 66%
“…Earlier research suggested that noise has great effects on the dynamic activity of the system [57,58]. In our study, the minor effects of noises on the system mainly refer to the characteristics of the system such as the bistable phenomenon of the rate equation exhibited.…”
Section: Discussionmentioning
confidence: 73%
“…Many theoretical models consider that two cells with identical genotype express the same phenotype under identical environmental conditions. However cellular individual response is likely to differ among cells, despite they have identical genotype or not [16,17,18,20,21,22,23]. The cellular genotype does not determine cell behavior in a deterministic fashion but it rather works as an inherited starting profile stochastically sensitive to both external and endocrine influences [17,24,25].…”
Section: Importance Of Cellular Genotypes Heterogeneitymentioning
confidence: 99%